2016
DOI: 10.1021/acs.analchem.5b04661
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose-Based Biosensors for Esterase Detection

Abstract: Cellulose has emerged as an attractive substrate for the production of economical, disposable, point-of-care (POC) analytical devices. Development of novel methods of (bio)activation is central to broadening the application space of cellulosic materials. Ironically, such efforts are stymied by the inherent biocompatibility and recalcitrance of cellulose fibers. Here, we have elaborated a versatile, chemo-enzymatic approach to activate cellulosic materials for CuAAC "click chemistry", to develop new fluorogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…Moreover, Schyrr et al [ 31 ] have recently reported a fiber optic sensor based on the degradation of thin gelatin films which detect matrix metalloproteases at levels of 1–10 micrograms/mL, and also serve as a substrate to lower protease activity. These types of apparent noninvasive designs using modified hydrogels that allow unimpeded aqueous diffusion of the protease into the sensor/dressing matrix have similarities to a cellulosic approach for in situ detection of esterases reported by Derikvand et al [ 33 ]. Alternatively, we have previously proposed an approach utilizing a barrier to prevent uptake of the protease hydrolysis product (free fluorophore or chromophore) into the wound bed [ 23 ].…”
Section: Resultsmentioning
confidence: 84%
“…Moreover, Schyrr et al [ 31 ] have recently reported a fiber optic sensor based on the degradation of thin gelatin films which detect matrix metalloproteases at levels of 1–10 micrograms/mL, and also serve as a substrate to lower protease activity. These types of apparent noninvasive designs using modified hydrogels that allow unimpeded aqueous diffusion of the protease into the sensor/dressing matrix have similarities to a cellulosic approach for in situ detection of esterases reported by Derikvand et al [ 33 ]. Alternatively, we have previously proposed an approach utilizing a barrier to prevent uptake of the protease hydrolysis product (free fluorophore or chromophore) into the wound bed [ 23 ].…”
Section: Resultsmentioning
confidence: 84%
“…Paper functionalized with zinc oxide nanorods was used to preconcentrate myoglobin with enhanced performance compared to that of the unmodified paper [13]. A chemoenzymatic modification technology was developed to prepare paper-based fluorogenic esterase biosensors [26]. A wax-based technology was applied to modify hydrophobic patterns and hydrophobic barriers on paper using a wax printer [27] and a pen-writing approach [28].…”
Section: Introductionmentioning
confidence: 99%
“…These attractive properties, especially when coupled with chemical and/or physical modifications that influence function, provide a platform for the development of advanced materials based on cellulose. In fact, during the past several decades, studies have shown that surface modifications of cellulose produce functional surfaces that can be used for high‐value‐added applications in areas as diverse as composite materials, flexible organic electronics, biomedical applications, microfluidic devices, self‐cleaning surfaces, and oil–water separation systems …”
Section: Introductionmentioning
confidence: 99%
“…These attractive properties, especially when coupled with chemical and/or physical modifications that influence function, provide a platform for the development of advanced materials based on cellulose. In fact, during the past several decades, studies have shown that surface modifications of cellulose produce functional surfaces that can be used for high-valueadded applications in areas as diverse as composite materials, 7-10 flexible organic electronics, [11][12][13][14][15][16][17] biomedical applications, [18][19][20][21][22][23] microfluidic devices, 24,25 self-cleaning surfaces, 26 and oil-water separation systems. 27,28 Chemical reactivity of cellulose arises from three hydroxyl groups present in each anhydroglucose repeating unit of the cellulose macrostructure, which can be functionalized through esterification or etherification reactions.…”
mentioning
confidence: 99%